Stereoselective Synthesis of the β‐Amino Acid Moiety of Fijiolide A. Issue 6 (14th December 2018) - Kurzawa, Timon; Kerste, Eric; Nikodemiak, Paul; Bothe, Daniel; Harms, Klaus; Koert, Ulrich
Abstract : An enantioselective synthesis of the β‐amino acid moiety of fijiolide A is described. Starting from eugenol, two sulfamates could be obtained on gram scale as substrates for an enantioselective C–H amination using Rh2 ( R/S ‐nap)4 . Acylation and ring opening of the resulting oxathiazinanes, followed by stepwise oxidation of the corresponding amino alcohol and TES‐protection of the catechol gave rise to Cramer's amino acid fragment from the total synthesis of fijiolide A. Abstract : A stereoselective synthesis of the β‐amino acid moiety of the fijiolides was achieved using an intramolecular Du Bois' asymmetric C–H amination of a sulfamate.